2016
DOI: 10.1177/1756287216638592
|View full text |Cite
|
Sign up to set email alerts
|

Diseases masking and delaying the diagnosis of urogenital tuberculosis

Abstract: To the editor:We read with interest the article by Kulchavenya and Kholtobin on urogenital tuberculosis (UGTB) [Kulchavenya and Kholtobin, 2015], in which the authors provide information about unusual UGTB cases. While the authors claim that they have carried out a systematic review of the topic, we completely disagree with that statement. Systematic reviews represent the highest level of evidence available for making clinical decisions, particularly if they are based on high quality studies and a strict and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These surgeries damage fertility, and affected women may encounter surgical complications throughout their lives. The relationship between patients and their physicians can also deteriorate, leading to medicolegal issues 3,7 . However, few studies have reported differential diagnostic findings for the two diseases based on CT scans [12][13][14][15] .…”
mentioning
confidence: 99%
“…These surgeries damage fertility, and affected women may encounter surgical complications throughout their lives. The relationship between patients and their physicians can also deteriorate, leading to medicolegal issues 3,7 . However, few studies have reported differential diagnostic findings for the two diseases based on CT scans [12][13][14][15] .…”
mentioning
confidence: 99%